PENGARUH KONEKSI POLITIK, GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP TAX AVOIDANCE (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2020)
The purpose of the study was to test the influence of Political Connections, Good Corporate Governance, and Financial Performance on Tax Avoidance. The research method used is a quantitative method. The study used data of 45 manufacturing companies listed Index Stock Exchange (IDX) during the period 2014 to 2018. Samples are taken by the purposive sampling method and which meets the criteria for sample selection. Data is processed with Version 9 Eviews software using the Generalized Least Square (GLS) method. Results show that Political Connection and Financial Performance have a positive influence on Tax Avoidance, this suggests that there are still companies that practice tax evasion. Corporate Governance has no effect on Tax Avoidance, meaning the existence of Corporate Governance is effective in attempting to prevent tax avoidance practices.Â